PROTOTIPE KNOWLEDGE MANAGEMENT SYSTEM DALAM PENERIMAAN, PENYIMPANAN, DAN PENDISTRIBUSIAN ZAKAT BERBASIS WEB 2.0 - RUDI PRASETYA (LPPM, 2015)
Zakat Al-Hakim institutions engaged social mobilization duties, storing, and distribution of zakat funds that require the data muzaki deposit and mustahik charity, and employees who manage to cleanly to improve services to the public charity. In the process of administration of zakat management is currently running as is, and there is no system for gathering and storage and distribution of web-based charity. So this study builds a prototipe Knowledge Management System (KMS) using a web-based Unified Software Development (USDP) object oriented (Object Oriented Analysis and Design) Using Modeling Language (UML). Mechanical testing of the system with a black box testing approach. Quality tested software using Focus Group Discussion (FGD). The results of the study in the form of a prototype of a Knowledge Management System in the collection, management, and distribution of Zakat based on web 2.0 LAZ Al Hakim.Keywords: Knowledge Management System, Collection, Storage, Distribution of Zakat, Web 2.0, UML, Unified Software Development Process